Screening and formulation of novel carriers for Xanthomonas bacteriophage to control bacterial leaf blight disease - Liu, Jian; Wang, Huiling; Chia, Suet Lin; Tan, Geok Hun (Malaysian Society of Microbiology, 2022)
: This study was aimed to evaluate the potential of several carriers to formulate the phages and retain their activity under various pH and temperature conditions. Methodology and results: The skim milk, rice flour, corn flour and CalnuXan (calcium and magnesium) as carriers to formulate the isolated phage to maintain its activity under extreme pH and temperature conditions. Two phages formulated with carriers retained their viability at pH 5, pH 7 and pH 9 compared to that of the unformulated phages. Besides, the formulated phages also retained a high titre compared to the unformulated phages when they were exposed to 37 °C and 45 °C. Based on the in vitro study of the formulation, it was applied in the glass house. The plant height, leaf chlorophyll and disease scoring were recorded and analyzed. In the glass house, the rice plant treated with formulated phages showed higher plant height and chlorophyll content than those treated with unformulated or untreated phages. Nonetheless, both formulated and unformulated protected the rice plant, which showed lower disease severity than the untreated group. Conclusion, significance and impact of study: Phage therapy has been used for treating plant diseases caused by pathogenic bacteria. Despite their effectiveness in killing the pathogen in vitro, the results were not reproducible in the field. Bacteriophages (phages) are sensitive to environmental factors and infection efficiency was dropped when exposed to harmful environments. However, this study successfully formulated two novels Xanthomonas phages, as biocontrol agents against bacterial leaf blight (BLB) disease in rice.